The interest rate elasticity of credit demand and the balance sheet channel of monetary policy transmission in South Africa - Doig, Gregory Graham (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2026)
It has long been accepted that changes in monetary policy have real economic effects
Keywords: Monetary policy -- South Africa; Banks and banking -- South Africa; Bank loans -- South Africa; Finance -- South Africa; Vector autoregression (VAR) approach to econometric modeling; Financial statements; Interest rates -- South Africa